2022
DOI: 10.1155/2022/4974579
|View full text |Cite|
|
Sign up to set email alerts
|

Machine English Translation Evaluation System Based on BP Neural Network Algorithm

Abstract: In order to solve the problems of machine translation efficiency and translation quality, this paper proposes an English translation evaluation system based on the BP neural network algorithm. This method provides users with a more intelligent machine translation service experience. With the help of the BP neural network algorithm, taking English online translation as the research object, Google’s translation quality is the best, with an error frequency of only 167, while Baidu translation and iFLYTEK translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…References [21], [22], [50], [35], [78], [82], [83], [84], [85], and [91] provide a detailed analysis of machine translation pertaining to particular languages or dialects, including Arabic, Urdu, Sana'ani, and Moroccan Arabic. Furthermore, the evaluation and increase in machine translation quality were examined in [3], [21], [29], [32], [49], [58], [86], [75], [78], [80], [85], [87], and [92]. References [7], [6], [63], [87], [69], [82], [88], [89], and [90] pertain to the wider scope of artificial intelligence in translation, including aspects such as education and the influence on professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…References [21], [22], [50], [35], [78], [82], [83], [84], [85], and [91] provide a detailed analysis of machine translation pertaining to particular languages or dialects, including Arabic, Urdu, Sana'ani, and Moroccan Arabic. Furthermore, the evaluation and increase in machine translation quality were examined in [3], [21], [29], [32], [49], [58], [86], [75], [78], [80], [85], [87], and [92]. References [7], [6], [63], [87], [69], [82], [88], [89], and [90] pertain to the wider scope of artificial intelligence in translation, including aspects such as education and the influence on professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fuzzy logic and feature extraction algorithms in translation and language analysis was discussed in [60], [61], [62], [63], [67], [68], [69], [77], [79], [82], and [90]. Regarding Human Evaluation and Cognitive factors, it has been observed that references [71], [76], [78], [80], [81], [88], and [92] analyzed the significance of human evaluation and cognitive factors in assessing the quality of translation. Finally, a detailed exploration of ethics in translation and its associated considerations is encapsulated within references [93] through [98], presenting a comprehensive discourse on this critical subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their human error analysis also indicates that there is still room for improvement in NMT output. Similarly, Han and Meng (2022) evaluated the quality of Chinese-English online translation using the BP neural network algorithm. They found that Baidu translation and iFLYTEK translation have a much higher error rate than Google Translate.…”
Section: Quality Assessment For Neural Machine Translationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%